2008
DOI: 10.1161/atvbaha.107.152538
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Circadian Clock Rhythmicity Is Retained in the Absence of Adrenergic Signaling

Abstract: Objective-The incidence of heart attack and stroke undergo diurnal variation. Molecular clocks have been described in the heart and the vasculature; however it is largely unknown how the suprachiasmatic nucleus (SCN) entrains these peripheral oscillators. Methods and Results-Norepinephrine and epinephrine, added to aortic smooth muscle cells (ASMCs) in vitro, altered Per1, E4bp4, and dbp expression and altered the observed oscillations in clock gene expression. However, oscillations of Per1, E4bp4, dbp, and Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
44
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 37 publications
4
44
1
Order By: Relevance
“…33,34 However, this has not been reported in human AT until now. This persistence of in vitro gene expression oscillations strongly suggests its direct regulation by endogenous factors, which modulate the circadian expression of these genes in adipose explants in an autocrine manner.…”
mentioning
confidence: 89%
“…33,34 However, this has not been reported in human AT until now. This persistence of in vitro gene expression oscillations strongly suggests its direct regulation by endogenous factors, which modulate the circadian expression of these genes in adipose explants in an autocrine manner.…”
mentioning
confidence: 89%
“…Although these rhythms are mainly controlled by the suprachiasmatic nucleus of the hypothalamus, other peripheral tissues, such as muscle or liver, regulate their functions through the expression of their own clock genes (Cermakian and Boivin 2009). Indeed, the transcriptional program regulated by these genes appears to be highly tissue specific (Reilly et al 2008). In this respect, we have demonstrated that human adipose tissue (AT) expresses clock genes in both visceral (VAT) and subcutaneous (SAT) adipose tissues (Garaulet and Madrid 2009).…”
Section: Introductionmentioning
confidence: 92%
“…No direct evidence has been reported that catecholamine or nutrients (glucose or fatty acids) could affect the phase of circadian clock. 87 A recent report revealed that PPARg induces Bmal1 expression in cardiovascular organs, 43 suggesting that thiazolidinediones, an agonist of PPARg, may become a potential tool for manipulating the clock system.…”
Section: Roles Of the Peripheral Clock In Cardiovascular Diseasesmentioning
confidence: 99%